2013
DOI: 10.1111/plb.12073
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress does not protect Quercus ilex L. from ozone effects: results from a comparative study of two subspecies differing in ozone sensitivity

Abstract: Long-term effects of ozone (O 3 ) exposure and drought stress were assessed on two subspecies of Quercus ilex: ssp. ilex and ssp. ballota. Two-year-old seedlings were continuously exposed for 26 months in open-top chambers to three O 3 treatments: charcoal filtered air, non-filtered air and non-filtered air supplemented with 40 nlÁl À1 O 3 . Additionally, two irrigation regimes were adopted: half of the plants were wellwatered and the others received half of the water supplied to control plants. Growth, shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 46 publications
(59 reference statements)
4
49
2
8
Order By: Relevance
“…Further the defense processes may have been weakened by elevated O 3 concentration to an extent that a greater reduction in growth resulted (Matyssek et al, 2006;Tausz et al, 2007). There were similar reports about drought increases tree sensitivity to O 3 and the overall oxidative risk as well, such as Quercus ilex L. (Alonso et al, 2013), Pinus halepensis (Alonso et al, 2001) and poplar clones (Pollastrini et al, 2014). Although the results indicated that drought didn't protect biomass as well as gas exchange from adverse O 3 injury at the end because the effects of interaction were higher than any individual factor, ozone or drought.…”
Section: Combination Effects Of Elevated O 3 and Drought Stressmentioning
confidence: 80%
See 1 more Smart Citation
“…Further the defense processes may have been weakened by elevated O 3 concentration to an extent that a greater reduction in growth resulted (Matyssek et al, 2006;Tausz et al, 2007). There were similar reports about drought increases tree sensitivity to O 3 and the overall oxidative risk as well, such as Quercus ilex L. (Alonso et al, 2013), Pinus halepensis (Alonso et al, 2001) and poplar clones (Pollastrini et al, 2014). Although the results indicated that drought didn't protect biomass as well as gas exchange from adverse O 3 injury at the end because the effects of interaction were higher than any individual factor, ozone or drought.…”
Section: Combination Effects Of Elevated O 3 and Drought Stressmentioning
confidence: 80%
“…Drought did not protect trees from O 3 effects but further enhanced O 3 damage. It was reported that drought increase the sensitivity to O 3 (Pollastrini et al, 2014;Alonso et al, 2013) and slowed or even stopped stomata response to abrupt stresses (Paoletti, 2005), which may cause a stronger reduction and may actually increase the overall oxidative risk as well due to limited carbon fixation (Matyssek et al, 2006;Tausz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The assumption for which drought-induced stomatal closure would limit O 3 entering the leaf, and the consequent O 3 -triggered damage [10], seems not to be universally acceptable. In some cases, drought does not protect trees from the effects of O 3 but, conversely, further exacerbates O 3 damage [11]. In addition to the physiological status of plants under stress, analyses of cellular and metabolic rearrangements adopted by plants may provide complementing evidence to describe the role(s) of several metabolites (such as compatible solutes, osmoprotectants, low-molecular weight proteins, and antioxidants) in the adaptation/acclimation of plants to harsh environmental conditions, such as the intricate interactions between drought and O 3 [12].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, we can argue that EDU was able to mitigate the synergic effects of drought and O 3 , possibly by reducing the oxidative pressure caused by the interaction of the two stresses. In fact, although drought is known to protect plants from O 3 by inducing stomatal closure [11,59], recent studies have highlighted that, under certain conditions, drought can instead increase plant sensitivity to O 3 [13], particularly if it occurs later in the season, after O 3 uptake during spring [14]. It has frequently been reported that EDU is able to ameliorate oxidative stress through different mechanisms, involving the inhibition of Reactive Oxygen Species (ROS) production [64] or the enhancement of both enzymatic and non-enzymatic ROS-scavenging mechanisms [17,35,53].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, under drought conditions, stomatal conductance can be strongly reduced, consequently limiting O 3 uptake and protecting vegetation from potentially harmful O 3 concentrations [8,11,12]. At the same time, however, given that both factors act as oxidative stresses on plants, it may be difficult to establish a cause-effect relationship between O 3 and tree response under natural conditions, where drought may have important confounding effects [13][14][15].…”
Section: Introductionmentioning
confidence: 98%